Alternative thermal regenerative osmotic heat engines for low-grade heat harvesting. (15th March 2020) - Long, Rui; Zhao, Yanan; Luo, Zuoqing; Li, Lei; Liu, Zhichun; Liu, Wei
Abstract: Low grade heat below 80 °C could offer a considerable energy supply. The utilization for this energy is limited with existing heat-to-power technologies for rather small differences between the heat source and environment. To efficiently harvest such low-grade heat, an alternative kind of thermal regenerative osmotic heat engine (TROHE) is proposed, which employs power-driven separation processes that run at a lower temperature, and the salinity gradient power technologies for power extraction after heating. For a TROHE that employs the reverse osmosis in the solution separation process, and pressure retarded osmosis in the energy extraction process, a figure of merit for selecting appropriate solutions is proposed. Salt solutions with a smaller specific heat capacity and density, and higher solubility are preferred to achieve a larger heat-to-work conversion efficiency. When operating between 60 °C and 20 °C, a maximum energy efficiency of 1.4% was achieved at 7 M LiCl-Methanol solution with a regenerative efficiency 90%. With advances in high performance regenerators and membrane technologies, the proposed TROHE can offer an alternative way for efficiently utilizing the vast low-grade heat. Graphical abstract: Image 1 Highlights: A kind of thermal regenerative osmotic heat engine is proposed to utilize low grade heat below 80 °C. A figure of merit is proposed to select appropriate working salt solutions. The energy efficiency with LiCl-methanol solution is 84.8% larger than that with LiCl-water solution. When operating between 60 °C and 20 °C, a maximum energy efficiency of 1.4% is achieved.